A new AD/MDO approach to support product design - Irene Ferreira (2009)
Nowadays, due to its critical role regarding product cost and performance, as well as time to market, product design is considered to be at the new frontiers for achieving competitive advantage. Therefore, to face todays rapidly changing business environments, it is extremely important to adopt a systematic approach to product design, in order to avoid errors and consequently achieve shorter time-to market performances. In this context, we will describe a new approach to support product design, which links Axiomatic Design (AD) and Multidisciplinary Design Optimization (MDO), applied in an integrated way at the conceptual design and the detailed design stages, respectively. Firstly, the conceptual design stage is undertaken by AD, which is used to map Functional Requirements (FRs) with the corresponding Design Parameters (DPs). Even though we try to guarantee the Independence of FRs, as established by Axiom 1 of AD, if some remaining coupled relations subsist that is not prohibitive. Afterwards, the detailed design is carried out by MDO, considered to be an appropriate methodology to design complex systems through an adequate exploitation of interacting phenomena. The proposed approach is applied to the design of metallic moulds for plastic parts injection, since the mould makers sector involves constant design and production of unrepeatable moulds, where uncoupled design solutions, mostly due to technological and time reasons, arent common (this sector is strongly influenced by customers who place enormous pressures on lead-time and cost reduction). This application points out the high potential of improvement that can be achieved through the simultaneous improvement of mould quality, reliability and time to market.